2018
DOI: 10.1002/mame.201700593
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Finite Element Analysis of the Tensile Behavior of Electrospun Polymer Single Fibers

Abstract: In this paper, polymer single fibers are prepared by electro‐spinning technology with different solvent rations, and the micromechanics properties are investigated together with the finite element analysis. It is found that the tensile stress–strain curves of single fibers can be attributed to two kinds of trends, which are independent of the solvent ratios. A possible arrangement model of polymer chains within the electrospun fibers is proposed according to the tensile stress–strain curves and the mechanics t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Existing models of electrospun structures propose 2D solutions [41,42,44,56] or consist of separate two-dimensional layers [45,46]. We propose that the nature of interpenetrating layers resulting from the electrospinning process should be assessed with a 3D approach to account for interlayer interactions between fibres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing models of electrospun structures propose 2D solutions [41,42,44,56] or consist of separate two-dimensional layers [45,46]. We propose that the nature of interpenetrating layers resulting from the electrospinning process should be assessed with a 3D approach to account for interlayer interactions between fibres.…”
Section: Discussionmentioning
confidence: 99%
“…While multiple studies have reported FE models of scaffolds produced by various techniques, there are limited publications on modelling three-dimensional mats made by electrospinning [ 41 , 42 ]. Yin and Xiong presented a parametric microscopical FE model of electrospun mat consisting of single nanofibres assuming that a single layer yields results comparable to the entire structure [ 43 ].…”
Section: Introductionmentioning
confidence: 99%